Literasi Keuangan Mahasiswa : Pengaruh Faktor Gaya Hidup, Pembelajaran dan Pendidikan Keuangan - Agmallia, Ressy; Ramadhani, Annisa Rahima; Abdi, Wahyu; Azmi, Zul (Asosiasi Dosen Akuntansi Indonesia, 2022)
This study aims to analyze whether the variables of lifestyle, financial learning at university and financial education in the family affect students' understanding of financial literacy in order to obtain good financial management for the future. A total of 100 respondents who came from students of the Accounting study program were sampled. Respondents filled out questionnaires which were distributed randomly. The data were then analyzed using regression analysis. The results of this study indicate that the variables of lifestyle and financial learning at the university have a positive influence on students' financial literacy, while the financial education variable in the family does not have a positive effect on the financial literacy of students in the accounting study program, Faculty of Economics and Business, Muhammadiyah University of Riau.